Rhizobial diversity from stem and root nodules of Discolobium and Aeschynomene - Claudia Miranda Martins; Wardsson Lustrino Borges; José de Souza Costa Júnior; Norma Gouvêa Rumjanek (Acta Scientiarum. Agronomy, 2015)
Among the genera that exhibit stem nodulation, Aeschynomene and Discolobium are found in the Pantanal Mato-grossense (wetlands in the state of Mato Grosso, Brazil). Isolates obtained from the stem and root nodules of D. pulchellum, D. psoraleaefolium, D. leptophyllum and A. fluminensis were collected from various locations in the Pantanal de Poconé sub-region and phenotypically characterized and genotyped by restriction analysis of the 16S rDNA gene. Of the 282 isolates obtained from the stem and root nodules, 84.3% alkalized YMA media and 74.1% showed slow growth. No differences in either the phenotype or the genotype among the rhizobial populations isolated from the root or stem nodules of the species Discolobium and A. fluminensis were observed. Among the isolates obtained from D. pulchellum, there was a group that was not similar to any of the reference strains used, and most of the isolates analyzed by PCR-RFLP were similar to the genus Bradyrhizobium.